Bibliometric Analysis of the Adoption and Innovation of Agricultural Processing Technologies: A Global Perspective - Indriyani; Dyah Ayu Suryaningrum; Muh. Aniar Hari Swasono; If'all (West Science Interdisciplinary Studies, 2023)
The adoption and innovation of agricultural processing technology play a vital role in ensuring food security, sustainability, and competitiveness in the agricultural sector. This research presents a comprehensive bibliometric analysis of academic literature on agricultural processing technology adoption and innovation from a global perspective. The study aims to identify key research trends, influential authors, major research themes, and emerging areas of interest in this domain. The dataset was collected from reputable scholarly databases, and VOSviewer analysis was used to visualize co-authorship networks, keyword clusters, and citation impact maps. The results revealed seven distinct clusters of research themes, including agricultural enterprise and innovation policy, market competitiveness, quality of food processing technology, technology innovation for rural development, sustainable development, technology transfer, big data in agriculture, and agribusiness and innovation technology. Moreover, ten highly cited research papers were identified, signifying their significant impact on the field. The findings offer valuable insights for policymakers, researchers, and industry stakeholders to enhance agricultural productivity, promote sustainable practices, and foster technology-driven innovations for a resilient global food system.